Unlocking the Potential of Technology: Estimating Nitrogen Requirement in Corn Using Optical Sensors - Lakesh K. Sharma; Diego A. H. de S. Leitão; Hardeep Singh (EDIS, 2025)
In the domain of agriculture, the application of optical sensing technology has become increasingly prevalent in the assessment of corn grain production. However, it is notable that comprehensive research endeavors addressing the efficacy of employing the Normalized Difference Vegetation Index (NDVI) as a predictive tool for corn grain yield in the specific context of Florida remain limited. To address this gap in knowledge, a dedicated study focusing on nitrogen (N) rates was meticulously designed in 2022. The primary objective of this study was to provide critical insights and empirical evidence to both our extension agents and the community of corn farmers. Its overarching aim is to elucidate the practical utility of NDVI sensors in forecasting crop output and facilitating precise estimations of N requirements.